TOTAL HEMOCYTES, GLUCOSE HEMOLYMPH, AND PRODUCTION PERFORMANCE OF SPINY LOBSTER Panulirus homarus CULTURED IN THE INDIVIDUAL COMPARTMENTS SYSTEM - Rifqah Pratiwi; Eddy Supriyono; . Widanarni (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Cannibalism can cause high mortality in a lobster culture. To prevent cannibalism, an artificial shel-ter is needed like the individual compartments system (ICS) to ensure that there is no contact bet-ween lobsters. This study aimed to evaluate the application of ICS on total hemocytes glucose hemo-lymph, production performance, and determine the shape of more effective ICS to minimize stress level of lobster. The treatments used for various application shape of ICS was tubular ICS, triangle ICS, square ICS, and shelter PVC pipes as control. Lobster maintenance was conducted in outdoor for 60 days. The results indicated that physiological responses with square ICS treatment were more effective to reduce stress level compared with other treatments (p<0.05). Application of ICS was more optimal to improved SR (p<0.05) and growth of lobster (p>0.05). Overall, treatment of square ICS was opti-mal related to production performance i.e. SR 88.89±5.24%, SGR 0.61±0.49%/day, with harvest size of total length 137.31±8.11 mm/ind, weight 58.83±4.78 g/ind, and FCR 22.71±1.72. Application of ICS in lobster culture was effective to reduce stress level as indicated from total hemocytes and gluco-se hemolymph, and support optimal production performance. Lobster culture using a square ICS sha-pe was effective to minimize stress level, compared with tubular ICS and triangle ICS.Keywords: cannibalism, glucose, hemocytes, individual compartments system, lobster, production